Preleukemia and Leukemia-Initiating Cell Activity in inv(16) Acute Myeloid Leukemia - Pulikkan, John Anto; Castilla, Lucio Hernán (Frontiers in Oncology, 2018)
Acute myeloid leukemia (AML) is a collection of hematologic malignancies with specific driver mutations that direct the pathology of the disease. The understanding of the origin and function of these mutations at early stages of transformation is critical to understand the etiology of the disease and for the design of effective therapies. The chromosome inversion inv(16) is thought to arise as a founding mutation in a hematopoietic stem cell (HSC) to produce preleukemic HSCs (preL-HSCs) with myeloid bias and differentiation block, and predisposed to AML. Studies in mice and human AML cells have established that inv(16) AML follows a clonal evolution model, in which preL-HSCs expressing the fusion protein CBF-SMMHC persist asymptomatic in the bone marrow. The emerging leukemia initiating cells (LICs) are composed by the inv(16) and a heterogeneous set of mutation. In this review we will discuss the current understanding of inv(16) preleukemia development, and the function of CBF-SMMHC related to preleukemia progression and leukemia initiating cell activity. We also discuss important open mechanistic questions in the etiology of inv(16) AML.